PERHITUNGAN BURN UP PEB U3Si2/Al DENSITAS 4,8 gU/cm3 PASCA IRADIASI POTONGAN BAGIAN MIDDLE - Ginting, Aslina Br.; Supardjo, Supardjo; Yanlinastuti, Yanlinastuti; Indaryati, Sutri; Boybul , Boybul (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
BURN UP CALCULATION OF THE MIDDLE PART OF IRRADIATED U3Si2/Al FUEL PLATE WITH 4.8 gU/cm3 DENSITY. Post-irradiation examination with non-destructive and destructive methods is required to study the performance of U3Si2/Al fuel during irradiation at the G. A. Siwabessy Multipurpose Reactor (RSG-GAS). The purpose of the burn-up calculation is to discover the 235U content that burned in a fuel plate of U3Si2/Al during use in RSG-GAS and to prove the burn-up obtained using destructive method by calculation using Origen Code. Therefore, this research performed a burn-up calculation of U3Si2/Al fuel plate (with a density of 4.8 gU/cm3) using destructive method through physicochemical analysis. The physicochemical analysis was aimed to determine the isotope content of 235U, 134Cs, and 137Cs in the irradiated U3Si2/Al fuel plate. The fuel plate was cut at the middle using a diamond cutting machine in a hot cell to obtain a sample cut with a weight of M-1 = 0.056 g, and a duplicate cut was also prepared with a weight of M-2 = 0.075 g. The sample was then dissolved using HCl 6 N and HNO3 6N. The results of dissolution was UO2(NO3)2 solution containing isotopic fission such as cesium and uranium. The solution of UO2(NO3)2 was pipetted at 1 mL and then transferred from the hot cell to R.135 (outside the hot cell) to separate 134Cs and 137Cs from 235U by a cation exchange method using zeolite from Lampung. The solution of UO2(NO3)2 was pipetted at 100 µL into a vial in duplicates and then 1000 mg zeolite was added. The cation exchange process was then carried out by stirring for 1 h. The separation process resulted in 134Cs and 137Cs isotopes in the solid phase, while uranium isotopes (238U, 235U, 234U), plutonium (239Pu, 238Pu) and other isotopes were in the liquid phase. Separation of uranium from other isotopes was done by anion exchange column method using 1200 mg of Dowex resin. The isotope content of 235U, 134Cs, 137Cs, 239Pu, and 238Pu was then measured using α/- spectrometer, the values of which were subsequently used for burn-up calculation. The result of the burn up calculation is 41.6565 ± 1.687%. The value of burn-up is not significantly different from the burn-up obtained from the calculation using Origen Code, which is 40%.